Transient infantile hyperthyrotropinaemia. Report of a case. Issue 12 (December 1979) - Miyai, K; Amino, N; Nishi, K; Fujie, T; Nakatani, K; Nose, O; Harada, T; Yabuuchi, H; Doi, K; Yamamoto, T; Satake, R; Tsuruhara, T; et al.
Abstract : A case of transient hyperthyrotropinaemia was found by mass screening for neonatal hypothyroidism using the paired TSH assay method. The patient was a baby boy born at term after a normal pregnancy who grew without any abnormal signs or symptoms. For the first 7 months after birth, his serum TSH was abnormally high while his total serum T4, T3, and free T4, T3 were within normal limits, exept for slightly low free T4 level at 7 months. The raised serum TSH decreased spontaneously to within normal limits after he was 9 months old.